Simulation of filtration problems on hybrid computer systems - Morozov, D. N.; Trapeznikova, M. A.; Chetverushkin, B. N.; Churbanova, N. G. (Mathematical models and computer simulations, 2013)
The paper is devoted to the use of super-high performance hybrid computer systems for problems of mathematical physics. A program system for simulation of multi-phase filtration processes is described, allowing activation of the entire potential of multicore supercomputers with graphics accelerators. In the case of test computations of the problems of infiltration, it is shown that the logical simplicity of the suggested computation algorithms and implementation program significantly speed up computations.